Critical Literature Review on Moral Education System in Indonesia: How Islamic Education and Pancasila Education Monopolize Morality in Schools - Husaeni, Mohammad Fahri (UIII Press, 2023)
Moral education continues to be a subject of extensive debate within the field of education due to the challenges it poses in both pedagogical implementation and philosophical foundations. This study aims to provide a comprehensive critical review of Indonesia's moral education system by examining its teaching practices in schools and exploring its sociological and structural function within society. This study focuses specifically on Islamic and Pancasila education in Indonesia. To achieve this objective, a semi-systematic literature review approach is employed, incorporating peer-reviewed articles to gather relevant information. This study also employed Critical Discourse Analysis (CDA), which enables an analysis of power dynamics and discursive relationships within the realm of moral education in Indonesia. By incorporating the theoretical frameworks proposed by Durkheim's Moral Education and Bourdieu's social capital theory, this study identifies key themes that provide valuable insights into the development and implementation of moral education. This research explores moral education as a means of fostering social integration and social capital that serves to maintain the existing status quo. By examining these aspects, this research offers valuable insights into the role of education as a sociological function that operates within the power structure, and critically assesses the extent of the state’s involvement in the implementation of moral education.